Optimization of Investigation of the Sragen Police General Criminal Investigation Bureau in the Crime of Vehicle Theft - Rajagukguk, Davidson (Advances in Police Science Research Journal, 2024)
This research is motivated by data on the high number of vehicle theft crimes at the Sragen Police, accompanied by the lack of completion of these crimes in the last 3 years. Polri has the duty to enforce the law based on Law Number 2 of 2002 concerning the Police of the Republic of Indonesia which is carried out by the function of Reserse Criminal. This study aims to determine the implementation of the investigation into the crime of vehicle theft by the General Crime Investigation Unit at the Sragen Police. To process the data, the authors use management theory as well as concepts and laws governing the procedures for conducting criminal investigations. This research was conducted with a qualitative approach, the type of action research and data collection techniques with interviews, observations, and document studies. The results of the study indicate that the main obstacle in conducting investigations into the crime of vehicle theft is at the stage of searching for suspects and/or looking for evidence. It is influenced by several factors, namely internal and external factors of the organization. Internally, the organization includes general investigation unit personnel, investigation methods and facilities and infrastructure owned by the Sragen Police General Research Unit. While externally, namely the facilities at the Crime Scene as a supporting factor and difficult evidence, the technique of the perpetrator, and the reporting party who cannot provide supporting evidence for the crime. Based on the research results, the authors suggest empowering personnel, supporting facilities and infrastructure from the National Police, collaboration between internal and external parties, innovating motorized vehicle tracking devices, and using the latest technology to help trace perpetrators and evidence.